Implementation of the Singing Method to Understand Unggah-Ungguh Basa in Javanese Language Learning in Middle School - Hasanah, Eryneta Nurul; Nurhayati, Endang (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Javanese language ethics are part of learning Javanese, which is considered difficult for students to learn. The language levels in the variety of ngoko and krama make students confused in their applications. Rigid learning also makes it harder for students to memorize Javanese ethics vocabulary. The singing method poses an easier and more interesting solution to learning Javanese language ethics. This study aimed to describe the implementation of the singing method and its implications for learning Javanese language ethics in class. This study used the descriptive-qualitative method. The research data were obtained from observations and interviews with Javanese language teacher informants at Public Junior High School 1, Selorejo. Data collection techniques included observation and structured interviews. Data analysis was carried out through data collection, data condensation, data presentation, and drawing conclusions. The results showed that the learning method of singing included the preparation, implementation, and evaluation stages. The singing method stimulates students’ optimal development to understand the proper application of Javanese language ethics. This is shown by the ability of students to correctly differentiate the application of Javanese language ethics based on their variety and level. Thus, the singing method can be applied to learning Javanese language ethics at school.